The Relevance of Large Language Models for Project Management - Stamatis Karnouskos (IEEE Open Journal of the Industrial Electronics Society)
The rise of artificial intelligence, particularly the emergence of large language models (LLMs) like ChatGPT, continuously reveals numerous advantages across various domains. However, the area of project management has not yet been sufficiently explored. This study fills the research gap by conducting an empirical evaluation of three well-known LLMs: OpenAI's ChatGPT-3.5 and ChatGPT-4, as well as Google's Bard. The evaluation involves subjecting these LLMs to tests designed to prepare professionals for project management certification by the Project Management Institute. The findings cast a positive light on all three LLMs, with each model achieving scores exceeding 82%. Key insights acquired include: LLMs demonstrate the ability to effectively answer project management certification exam questions; LLMs and project managers should be viewed as a dynamic and complementary partnership; and project management certification should evolve to include an assessment of how project managers collaborate with LLMs to enhance project management.